The Effect of Using E-Learning Media on Students’ Learning Motivation - Dian Agustina Dalimunthe (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
The decreased enthusiasm of students to study online is the background of this research. The purpose of this study was to determine the effect of using e-Learning media on the learning motivation of Medan State University students. This research was classified into quantitative research with a correlational approach. Unimed Catering students who have studied using e-learning are used as the research population. While the number of respondents for the research data was 96 people and the respondents for the trial data were 30 people. The number of respondents was obtained using the Slovin method. The sampling technique used was random sampling, in which the names of the samples were randomized at the time of distributing the questionnaires. The instrument used to collect the research data was a questionnaire which was arranged based on a Likert scale which had been tested for validity and reliability. The research data were then processed using SPSS 24. Based on the results of the study, the correlation value between the independent variable and the dependent variable was 0.525 which means that it has a correlation and regression coefficient x of 0.744. This value explains that with every 1% increase in the value of using e-Learning media, the value of student learning motivation will increase by 0.744. The influence between the independent variable and the dependent variable looks positive because the regression coefficient has a positive value. Furthermore, to test the hypothesis, a comparison of the t value is also carried out with the t table. The t value obtained is 4.931> 1.68 so it can be concluded that Ho is rejected and Ha is accepted.